ANALISIS PERBANDINGAN HARGA POKOK PRODUKSI MAKLON DAN HARGA POKOK PRODUKSI SECARA MENYELURUH (STUDI KASUS PADA ICYLAND APPAREL) - Fathur Adrianto; Nur Hisamuddin; Ririn Irmadariyani (Universitas Jember, 2017)
This research aims to know the implementation of generally accepted accounting principles of substance over form of the village’s financial management and the impact of not satisfy the principle of substance over form against the trend of lapses in Financial Management Kalimadu Jember Regency Village. This research is qualitative research in methods of case studies. Primary data obtained by the method of in-depth interview to some villagers. The secondary data were directly obtained from the Government of the Kalimadu Village. The validity test was using the technique of triangulation of Data sources. The results showed that the substance over form principle wasn’t applied in every process of financial management of the village. This is impacting on the quality of the financial report of the Kalimadu village of unaccountable and could not be accounted for so that gave rise to the existence of the lawsuit to the village head and village treasurer. Keywords: Cost of Goods Sold, Production Cost, Cost